A pH/Ultrasound dual-response biomimetic nanoplatform for nitric oxide gas-sonodynamic combined therapy and repeated ultrasound for relieving hypoxia. (February 2020) - An, Jie; Hu, Yong-Guo; Li, Cheng; Hou, Xiao-Lin; Cheng, Kai; Zhang, Bin; Zhang, Ruo-Yun; Li, Dong-Yu; Liu, Shao-Jun; Liu, Bo; Zhu, Dan; Zhao, Yuan-Di
Abstract: Sonodynamic therapy (SDT) has rapidly developed as a powerful alternative to traditional photodynamic therapy due to its intrinsically deeper tissue-penetration. However, single SDT dose is incapable of radical cure because the long-term hypoxia of tumor limits its therapeutic effect. Herein, we developed a biomimetic nanoplatform with dual pH/ultrasound response, homologous targeting and low phototoxicity for combined nitric oxide (NO) gas therapy with SDT to solve the problem. This nanoplatform is composed of zeolite imidazole framework-8 material embedded with nitrosoglutathione (GSNO) and chlorin e6 (Ce6) by one-step encapsulation, and then wrapped by homologous tumor cell membrane. In vitro and in vivo experiments indicate that the biomimetic nanoplatform has excellent biocompatibility and shows higher retention in tumor by homologous targeting. Importantly, it can sustainably release the encapsulated drug in acidic tumor microenvironment and accelerate degradation by ultrasound (US). Furthermore, NO released from GSNO and reactive oxygen species generated by Ce6, which are both triggered by US, react with each other to produce highly reactive peroxynitrite to inhibit the growth of tumor. Moreover, by repeated US irradiation, the tumor hypoxia can be relieved for a much-longer term, resulting in an effective gas-sonodynamic combined treatment. This study fully utilizes the advantages of US, providing a new strategy for high-performance cancer therapy.